Analisis Performa Sumur Apt-017 Berdasarkan Data Sonolog & Dynagraph di Lapangan Sangatta Field - Niagra Portibi Dolokdaribu; Syarifudin Nur Wahit; Jeremi Devito (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Declines in well performance in mature fields are often caused by complex interactions between fluid conditions and the performance of artificial lift systems. This study aims to analyze the performance of Well APT-017 in the Sangatta Field using Sonolog and Dynagraph data through the SODYNA integration approach. The data used includes production data, fluid level measurements, and pump cards from field testing. The analysis results show that production decreased from 18–20 BOPD to 10–12 BOPD. Sonolog indicates that the fluid level is at a depth of 967.31 ft with gas-cut fluid conditions, while Dynagraph indicates gas interference, low pump fillage, and signs of valve leakage. The integrated results of both methods show that fluid is present, but its quality does not support optimal pump performance. This study recommends optimizing the pumping system and gas control to improve well production efficiency.